OPTIMIZATION FOR THE VIBRATION FATIGUE DURABILITY OF MOTOR CONTROL UNIT OF NEW ENERGY VEHICLE - LU Gang; CHEN Jian Ming; SHEN Ding Jian; MAO Hong Feng (Jixie qiangdu)
The vibration failure issue of the motor control unit during the vibration test was studied,and the reasons of the failure were analyzed by applying spectrum analysis method,the results showed that the coupled vibration is the main reason of the vibration failure. The optimization schemes against this problem were designed,the octave criterion was applied to design the component for avoiding coupled vibration,and the damping was increased to decrease the peak of the vibration response. The optimization schemes were verified by simulation and experiment,the results showed the vibration acceleration decreased by 23% ～ 31% using octave criterion design,and decreased by 25% ～ 34% through increasing damping. The conclusion can be drawn that two optimization ways can decrease vibration acceleration level obviously,and the fatigue durability of the product was improved.